Aplikasi E-Learning Berbasis Android sebagai Media Pembelajaran Bahasa Pemrograman - Mutiwiyati, Mutiwiyati; Syaban, Rahul; Kurniasari, Endah; Oktaviani, Oktaviani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Advances in information technology can be used as a supporting medium in the learning process, one of which is E-learning. Programming language E-learning applications can be used to facilitate the process of learning programming languages. The application developed is based on Android and includes facilities such as downloading material presented in video form, quiz questions, forums for asking questions, and user profiles. The process of making the application uses a framework from JavaScript, namely React-Native as the front-end and Express JS as the back-end for the API provider, and MySQL as the database. The system development method used is the waterfall method. The stages of system development in this study started from planning problem identification and data collection, problem analysis and analysis of functional and non-functional requirements, application design using UML diagrams, application implementation by writing program code using React Native, Express Js, and MySQL, and trials by using 5 android devices. Based on the test results, it can be concluded that this application can run well and smoothly on devices with minimum specifications, namely Android version 6 with a resolution of 720 x 1280 and 2 GB of RAM. The test results show that the application can run properly and has a full-screen interface on each device, and can run smoothly without any bugs and errors.Keywords: Application, Android, Programming Language, E-learning.